Signaling events induced by lipopolysaccharide-activated Toll in response to bacterial infection in shrimp - Wang, Sheng; Li, Haoyang; Li, Qinyao; Yin, Bin; Li, Sedong; He, Jianguo; Li, Chaozheng (Frontiers in Immunology, 2023)
Toll-like receptors (TLR) play a crucial role in the detection of microbial infections in vertebrates and invertebrates. Mammalian TLRs directly recognize a variety of structurally conserved microbial components. However, invertebrates such as Drosophila indirectly recognize microbial products by binding to the cytokine-like ligand Spätzle, which activates signaling cascades that are not completely understood. In this study, we investigated the signaling events triggered by Toll in response to lipopolysaccharide (LPS), a cell wall component of gram-negative bacteria, and Vibrio parahaemolyticus infection in the arthropod shrimp Litopenaeus vannamei. We found that five of the nine Tolls from L. vannamei bound to LPS and the RNAi of LvToll1, LvToll2, LvToll3, LvToll5, and LvToll9 weakened LvDorsal-L phosphorylation induced by V. parahaemolyticus. All nine Tolls combined with MyD88 via the TIR domain, thereby conferring signals to the tumor necrosis factor receptor-associated factor 6 (TRAF6)-transforming growth factor-β activated kinase 1 binding protein 2 (TAB2)-transforming growth factor-β activated kinase 1 (TAK1) complex. Further examination revealed that the LvTRAF6-LvTAB2-LvTAK1 complex contributes to Dorsal-L phosphorylation and nuclear translocation during V. parahaemolyticus infection. Overall, shrimp Toll1/2/3/5/9–TRAF6/TAB2/TAK1–Dorsal cascades protect the host from V. parahaemolyticus infection, which provides a better understanding of how the innate immune system recognizes and responds to bacterial infections in invertebrates.